Plant bioregulators on common bean cultivated under two soil moisture - Ferreira, Miller Henrique; Nobre, Danúbia Aparecida Costa; Macedo, Willian Rodrigues (Revista de Ciências Agroveterinárias, 2020)
Restrictions on water available lead to possible damages in the bean crop, and the use of bioregulators can improve the plant signal and boost tolerance against drought stress. This study aimed to characterize physiological, biochemical, and biometric alterations in bean plants subjected to foliar application of bioregulators under different soil water levels. The following treatments were applied: control (water) and three bioregulators (5 μM of abscisic acid - ABA, 50 μM of methyl jasmonate – MeJA, and 5 μM of ABA + 50 μM of MeJA). Also, the plants were subjected to two soil water levels (60 and 80% of field capacity), in a 4 x 2 factorial scheme. The variables studied were: content of photosynthetic pigments, leaf gas exchange, and biometric indexes in the common bean plants. Our results showed that the ABA + MeJA treatment increased the concentration of chlorophyll b, ascorbate peroxidase (APX), and catalase (CAT) activities. At the same time, the photosynthetic rate was stimulated by the mixture of bioregulators on 36 days of planting (DAP). ABA and MeJA, applied isolated, caused a higher photosynthetic rate in the bean in the 34 DAP, whereas for the biometric variables, they were only influenced by the soil water levels. Regarding the biochemical mechanisms, it was verified that the ABA + MeJA treatment increased the activity of antioxidant enzymes and improved gas exchange responses in a condition of lower water availability. The bioregulators assessed in this research are beneficial in the modulation of plant physiology in plants under drought stress. However, the adequate water supply represents a better development of the plants.